Kilka uwag o kontrastywnej analizie stylu - Prokop, Izabela (Scripta Neophilologica Posnaniensia, 2019)
A few remarks on the contrastive analysis of style The phenomenon of style, analysed from different points of view, has been presented in this article. On the one hand, connections between stylistics and pragmalinguistics with the psychological profile of the sender have been indicated. Janusz Reykowski’s distinction of the five levels of centralisation, included in his publications, has turned out to be most useful in the pragmalinguistic analysis while describing the locutionary act, including the stylistic phenomena. On the other hand, though, a question about the possibility and limits of the reflection of style in translation has been asked, using the text example in a German-Polish pair, and working out the criteria of evaluation. In the conclusion of the article the author is postulating the formation of a German-Polish contrastive stylistics.